Phenomenological Description of Elderly Quality of Life in Family Settings: Deskripsi Fenomenologis Kualitas Hidup Lansia dalam Lingkungan Keluarga - Mohammad Izzan Fahrozy; Lely Ika Mariyati (Academia Open, 2025)
General Background: Aging is a final developmental stage characterized by physical and psychological decline that challenges individual well-being. Specific Background: In Indonesia, the growing elderly population requires greater attention to quality of life across social, psychological, spiritual, environmental, independence, and self-empowerment domains. Knowledge Gap: Previous studies predominantly employ quantitative approaches, leaving limited phenomenological insight into elderly individuals living with family. Aims: This study aimed to describe the quality of life of elderly residents in Banjarbendo Village using a qualitative phenomenological approach. Results: Findings from two elderly participants revealed generally positive quality of life, reflected in sustained social relationships, emotional regulation, functional independence, spiritual engagement, adaptive self-empowerment, and supportive living environments. Participants demonstrated gratitude, self-acceptance, low stress levels, and continued participation in daily and religious activities despite age-related limitations. Novelty: This research provides in-depth experiential evidence of six integrated quality-of-life domains among family-dwelling elderly individuals. Implications: The findings highlight the importance of family support, spiritual practice, and accessible environments in promoting meaningful aging and may inform community-based interventions and psychosocial services for older adults. Keywords: Elderly Quality of Life, Phenomenological Study, Psychological Well-being, Spiritual Well-being, Social Support Key Findings Highlights: Elderly participants maintained emotional stability and gratitude despite physical decline. Family interaction and religious practice supported daily functioning. Environmental accessibility contributed to continued independence.